2001
DOI: 10.1253/jcj.65.300
|View full text |Cite
|
Sign up to set email alerts
|

Response of the Stroke Volume and Blood Pressure of Young Patients With Nonobstructive Hypertrophic Cardiomyopathy to Exercise

Abstract: Stroke volume (SV), cardiac output (CO) and systolic blood pressure (SBP) were measured during maximal symptom-limited bicycle exercise testing in 13 young patients (age, 11-26 years) with nonobstructive hypertrophic cardiomyopathy (HCM). SV was measured by impedance plethysmocardiography; %SVend, %COend, and %SBPend represent the ratio of the value at termination of the exercise to the respective value at rest. In all patients of HCM-I (the Cardiac Event Group, 3 patients) and 3 of HCM-II (the Non-Cardiac Ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…34 , 35 They are unable to increase their stroke volume during exercise, and stroke volume might even fall secondary to a decrease of atrial contribution to preload. 36 39 Patients with abnormal blood pressure response to exercise have particularly marked reduction in stroke volume during exercise. 36 , 37 , 39 Exercise aggravates the relative disproportion between duration of systole versus duration of diastole with disproportionate shortening of diastolic filling time.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…34 , 35 They are unable to increase their stroke volume during exercise, and stroke volume might even fall secondary to a decrease of atrial contribution to preload. 36 39 Patients with abnormal blood pressure response to exercise have particularly marked reduction in stroke volume during exercise. 36 , 37 , 39 Exercise aggravates the relative disproportion between duration of systole versus duration of diastole with disproportionate shortening of diastolic filling time.…”
Section: Discussionmentioning
confidence: 99%
“… 36 39 Patients with abnormal blood pressure response to exercise have particularly marked reduction in stroke volume during exercise. 36 , 37 , 39 Exercise aggravates the relative disproportion between duration of systole versus duration of diastole with disproportionate shortening of diastolic filling time. 40 , 41 However, as therapy with propranolol has been reported to improve diastolic dysfunction in adult patients with hypertrophic cardiomyopathy, 41 , 42 and will allow longer diastolic filling time, there are potential mechanisms for β-blocker therapy to improve stroke volume on exercise in hypertrophic cardiomyopathy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Because patients with HCM may not show any significant functional impairment at rest, optimal assessment requires exercise testing [7]. An abnormal blood pressure [8][9][10] and stroke volume [9] response during exercise is a risk factor for sudden cardiac death in HCM patients. Nagata et al [11] reported that abnormal blood pressure response occurred in 11% of their patients with HCM and was associated with a high prevalence of cardiac events.…”
mentioning
confidence: 99%